Analysis of Composition and Structure of Riparian Vegetation In The Batang Arau River Flow Region, Padang City, West Sumatera - Yuni Selfia; Vauzia (Jurnal Serambi Biologi, 2021)
Abstract. In the watershed ecosystem, riparian vegetation is one component that plays a role in influencing the ability of the soil to absorb and maintain water quality. The Batang Arau watershed is the most polluted river in the city of Padang, due to changes in land use which cause damage to the vegetation ecosystem. So that the impact on the loss of composition, structure and ecological function. Based on this, it is necessary to conduct research to determine the composition and structure of riparian vegetation in the Batang Arau watershed. The research was conducted from 26 December 2020 - 2 February 2021, in the Batang Arau watershed which includes station 1 (factory area), Station 2 (plantation area), Station 3 (unspoiled area). The method used is Linear Systematic Sampling. The results showed that in the factory area there were 64 individuals with 21 species belonging to 12 families. In the field area, 80 individuals were found with 38 species in 27 families. Unspoiled areas obtained 89 individuals with 58 species belonging to 26 families. INP results show that the area is dominated by Homalanthus papulneus plants. Factory area diversity index (H') = 0.69. Field area (H') = 1.34. Unspoiled area (H') = 1.20.